Another milestone for UMP’s IT development - UMP, PNC
University Malaysia Pahang (UMP) continues to record success in the field of information technology (IT) with the signing of another Memorandum of Understanding (MOU) by its wholly-owned subsidiary, UMP Holdings Sdn Bhd (UMPH), with six selected software suppliers at the university’s Banquet Hall on January 29 last year.